2022
DOI: 10.1371/journal.pone.0268282
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective role of nitric oxide inhalation and nitrite in a Neonatal Rat Model of Hypoxic-Ischemic Injury

Abstract: Background There is evidence from various models of hypoxic-ischemic injury (HII) that nitric oxide (NO) is protective. We hypothesized that either inhaled NO (iNO) or nitrite would alleviate brain injury in neonatal HII via modulation of mitochondrial function. Methods We tested the effects of iNO and nitrite on the Rice-Vannucci model of HII in 7-day-old rats. Brain mitochondria were isolated for flow cytometry, aconitase activity, electron paramagnetic resonance, and Seahorse assays. Results Pretreatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…GSNO [ 25 , 26 ], BDNIC (binuclear DNIC), MDNIC (mononuclear DNIC) [ 27 ], and HbNO [ 28 ] were synthesized as previously described. Other chemicals were obtained from Sigma (St. Louis, MO, USA) as previously described [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…GSNO [ 25 , 26 ], BDNIC (binuclear DNIC), MDNIC (mononuclear DNIC) [ 27 ], and HbNO [ 28 ] were synthesized as previously described. Other chemicals were obtained from Sigma (St. Louis, MO, USA) as previously described [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The important role of nitric oxide system is due not only to neurotoxic, but also due to neuroprotective effect of NO [23], synthesized by eNOS, which acts as a vasodilator, participates in control of vasodilation and local blood flow, modulates processing of amyloid precursor protein (APP) affects functional state of microglia and cognitive functions [24]. Available data indicate a decrease in production of NO by endotheliocytes of human cerebral vessels causes an increased expression of APP and β-site of APP cleavage enzyme 1 (BACE1), which leads to an increase in secretion of β peptides (Aβ1-40 and Aβ1-42) of amyloid.…”
Section: Extrapolationmentioning
confidence: 99%
“…It has been found that short-term use of NO donors before the beginning of ischemia can protect the function of endothelium in ischemic reperfusion injury [46]. It was also shown that inhalation of NO or nitrite encourages brain function during perinatal hypoxic and chemical intervention [47].…”
Section: Introductionmentioning
confidence: 99%